Recovering Sight to the Blind in Luke 14:18. 19 - Tangkudung, Clarry Paul (Klabat Theological Review, 2021)
One of the tasks of the Messiah is to recover the blindness of human being.  Blindness is an important topic in the New Testament.  The act of recovering sight to the blind is the act of Messiah fulfilled by Jesus in his ministry.  This important task is prophesied in the Old Testament.  This prophecy is found in Isaiah 61: 1, 2.  The role of Jesus as Messiah is to recover the sight to the blind, to bring justice, and to give people righteousness.  Throughout the New Testament mentions the role of Jesus to recover the blindness.  The uniqueness of the word ‘blindness’ is that it is mentions together with the word ‘poor.’ Clear message is given to the people in the New Testament that Jesus given the power of the Holy Spirit to do these wonderful things.  There is strong connection of the ministry of Jesus to recover the sight to the blind and Sabbath.   Keywords:  Blindness; Messiah; Ministry; Sabbath References Barker, Kenneth L. ed.,  NIV Study Bible  (Grand Rapids: Zondervan, 1984), 1532 Walter Bauer, A Greek English Lexicon of the New Testament and Other Early Christian Literature, ed. Frederick W. Danker, 3 rd  ed. (Chicago: University of Chicago Press, 2000), BibleWorks. V.7. Beaulieu, Stephane.  Isaiah’s Messiah: Adventist Identity for the Last Days . Journal of the Adventist Theological Society, 27/1-2 (2016): 3-23), Available from http://archive.atsjats.org/Beaulieu%20BZ.pdf;  accessed at 12 August 2019 Betz, Hans Dieter.  The Sermon on the Mount: Hermeneia – A Critical and Historical Commentary on the Bible.   Augsburg Fortress: Minneapolis, 1995. Braun, Willi.   Feasting and Social Rhetoric in Luke 14 .  New York: Cambridge University Press, 1995. Bruno, Christoper R. “ Jesus is Our Jubilee” . . . But How?  The OT Background and Lukan Fulfillment of the Ethics of Jubilee.  Journal of the Evangelical Theological Society 53/1 81-101, March 2010 Carson.  D. A. Ed.  the Gospel According to John .  Apollos Leicester: England, 1984. Cranfield, C. B. E.,  the Gospel According to Saint Mark: An Introduction and Commentary .  Cambridge University Press: United Kingdom, 2000. Culpepper, R Alan.  Anatomy of the Fourth Gospel: A Study in Literary Design .  Fortress: Philadelphia, 1983.discipletree.com%2F05Courses%2FChurchGrowth%2F07Week%2FLuke%25204.16-20.doc), accessed at October 7, 2019 Fowler, James A.  A Commentary on the Revelation of John .  C.I.Y. Publishing Fallbrook: California, 2013. Fowler, James A.  Jesus Confronts Religion: A Commentary on the Four Gospel.  Christocentric Commentary Series. California: C.I.Y Publishing, 2006. Gaebelein, Frank E., Ed.,  Expositor’s Bible Commentary . Grand Rapids, Michigan: Zondervan Publishing House, 1984. Jordan, Richard.  Exegetical Notes on Luke 4:14-21  (Journal Online, available from: http://richardajordan.com/Bible_Study/luke4.pdf), accessed at June 12, 2019 Koech, Joseph.  the Spirit Motif in Luke 4:14-30; Acts 1:8 . African Journal of Evangelical Theology 27.2 2008. Monshouwer, D.  The Reading of the Prophet in the Synagogue at Nazareth.  en Bib 72 199. Nichol, Fancis, ed.  Seventh-day Adventist Bible Commentary. Rev. ed. Washington, DC: Review and Herald, 1976-1980. Park, Jim.  The Role of the Sabbath/Jubilee in Luke 4:16-18 .  Journal Online, available from:https://view.officeapps.live.com/op/view.aspx?src=http%3A%2F%2F Sanders, J. A.  From Isaiah 61 to Luke 4 , in Christianity, Judaism, and Other Greco-Roman Cults, ed. J. Neusner.  Leiden: Brill, 1975. Siker, Jeffrey S.  First to the Gentiles: A literally Analysis of Luke 4:16-30.   Journal of Biblical Literature III/1,  Loyola Marymount University, Los Angeles, CA 90045, 1992. Stevanovic, Ranko.   Revelation of Jesus Christ:  Commentary on the book of Revelation    Andrews University Press: Berrien Spring, Michigan, 2002. Steyn, J. & A. Yousaf, Jesus and the Marginalized: Attaching Pastoral Meaning to Luke 4: 14-30. Journal of Acta Theologia, February 2012. Turner, Max.  The Work of the Holy Spirit in Luke-Acts .  Journal Online, available from: https://pdfs.semanticscholar.org/c5c8/29f9ca024844d73a43aca40a0444d0765f6f.pdf. accessed at September, 13, 2019 Utley, Bob.  Study Guide Commentary Series New Testament, Vol. 3.   A .  Texas: Bible Lessons International, Marshall, 2004. Win, Adam.  The Purpose of Mark’s Gospel: An Early Christian Response to Roman Imperial Propaganda .  Mohr Siebeck, Tubingen: Germany, 2008.